Digital Literacy and Its Use by Teacher Trainess at Secondary Level in Odisha - Ramakanta Mohalik (RIRAI Publisher, 2020)
Digital devices and applications have been used in schools and teacher education institutes across the globe for teaching learning. All the prospective teachers must be digitally savvy to utilize it in school for teaching, assessment, management and professional development. This study intended to find out the level of digital literacy and its uses among teacher trainees at secondary level. Descriptive research method was followed for undertaking this study. Survey was conducted on sample of 170 trainees selected randomly from teacher education institutes under Utkal University, Odisha, India. Self developed questionnaire based on different aspects of digital devices and applications such as skills of trainees in digital technology, use of digital technology and applications by trainees for learning and teaching etc. was used at tool. Collected data were subjected to frequency and percentage analysis and accordingly conclusions were drawn. The study found that (i) majority of trainees can change screen brightness and contrast, minimize, maximize and move window screen, use search command to locate a file and download and install applications, (ii) more than 50% of trainees do not know learning management system, virtual worlds, podcasts and web design applications, (iii) around 70% of trainees are aware about storage of video in camera, manage junk mail and update username and password and less than 50% of trainees knew about voice typing and cyber security, (iv) majority of trainees use group email and whatsapp for academic work and only 20% of trainees use digital devices for using PPT in class, create digital learning materials, provide feedback to students. It is suggested that teacher education institutes must be equipped with digital devices and applications useful for teaching learning and professional development. Further, teacher educator must encourage and motivate trainees by integrated ICT in regular course work and across the subjects so that trainees can develop skills of using it for teaching, learning and assessment in schools.